Comprehensive integrated approach to evaluate biophysical and socio-economic benefits of the contour bunding technology in Mali and scaling it - CGIAR Research Program on Water, Land and Ecosystems (2019)
The Contour Bunding Technology has been successfuly tested at farm level and ready to be taken up at landscape wide scale